Promoting healthy eating standards on children through CSR educational programs: an evaluation of impact on eating preferences, attitude towards the brand and perceived brand reputation - Ferreira, Miguel Araújo Avelino de Sousa (2013)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics